Hypoplastic left heart syndrome: can this malformation be treated surgically?. Issue 5 (May 1980) - Milo, S; Ho, S Y; Anderson, R H
Abstract : A corrective technique for the surgical treatment of hypoplastic left heart syndrome is proposed. This technique is compatible with subsequent growth because it uses the patient's own tissues exclusively.